Surface Structure and Electronic Properties of Lu3Al5O12 - Weian Guo (MDPI AG, 2021)
Lu3Al5O12 (LuAG) is a famous scintillator that has the advantages of high efficiency, high light yield, and fast decay after being doped with active ions. F centers (oxygen vacancies with two electrons) and antisite defects are the most important defects and can greatly affect the scintillation performance in the bulk materials. However, the surface defects that strongly affect the spectrum of a single crystal (SC) and single crystal film (SCF) and the effect on the electronic properties have not been investigated. In this context, we investigate the surface structural and electronic properties of Lu3Al5O12 using first-principles calculations. The Lu atoms are six-fold and seven-fold coordinated with the O atoms on the S1 and S2 surfaces. The surface oxygen vacancies and antisites have considerably lower formation energies than for the bulk. The oxygen vacancies in the bulk introduce the occupied states in the band gap. The surface electronic states are mainly located on the oxygen atoms and can be eliminated via oxygen vacancies.